Festival of Kinship, Defiance, and Ethnic Survival - John Paul (Journal of Festive Studies)
In the fall of 2016, I traveled to North Dakota as an invited guest of the Standing Rock Sioux Tribe to document the emergent encampment of American Indians and their allies who had gathered to protest the construction of the Dakota Access Pipeline. This work explores some of these lived protests and the festival-like realities (as well as the strengths and criticisms of the "festival” notion) that were produced in such protestive actions. Ultimately, this article has three goals. First, it seeks to document, via photographs and text, some of the mobilization efforts of protesters against a segment of the oil and gas industry operating on American Indian land. Second, it questions the scholarly concept of "festival as protest"—again, highlighting the strengths and controversies of the application of this term to the Standing Rock Protests. Third, it shows how photography can complement and enhance qualitative field research.